Impact of COVID-19 Lockdown on Patients Undergoing Orthodontic Treatment: A Survey Based Study - Pirah Haque; Sadia Rizwan; Imtiaz Ahmed; Taskeen Khan; Hiba Tabassum; Sarfaraz Hussain (JLUMHS, 2023)
OBJECTIVE: To evaluate how the COVID-19 lockdown influenced patients receiving orthodontic therapy. METHODOLOGY: An Ambispective study was done by collecting the data from July to August 2022. An investigative questionnaire containing 17 questions was circulated to 325 respondents/patients. The data was collected using a convenience sampling technique. Patients undergoing orthodontic treatment with fixed appliances aged 18 to 40 years were included in the study. Both male and female respondents who participated in the survey varied in terms of their ages, i.e., between 18 to 40 years. Version 24 of a statistical package for social sciences (SPSS) has been used for data analysis. RESULTS: According to the study's findings, the lockdown's impact on patients undergoing orthodontic treatments was significant. For instance, anxiety & psychological distress were created during the lockdown because of concerns regarding the closure of hospitals and delayed visits to orthodontists or problems in getting appointments. Because of this, patients feared prolonged treatment durations and orthodontic emergencies, including discomfort, wires pinching them, ruptured skin, damaged brackets, ligature ties and bondable buccal tubes, etc. CONCLUSION: Due to covid-19 lockdown, patients found difficulty in their regular appointments or monthly checkups as the hospitals were closed. Patients also experienced mental distress, making it imperative to comprehend the psychology of individuals experiencing orthodontic care.